Pseudo-almost periodic and pseudo-almost automorphic solutions to some evolution equations involving theoretical measure theory - Diagana, Toka; Ezzinbi, Khalil; Miraoui, Mohsen (CUBO, A Mathematical Journal, 2014)
Motivated by the recent works by the first and the second named authors, in this paper we introduce the notion of doubly-weighted pseudo-almost periodicity (respectively, doubly-weighted pseudo-almost automorphy) using theoretical measure theory. Basic properties of these new spaces are studied. To illustrate our work, we study, under Acquistapace–Terreni conditions and exponential dichotomy, the existence of (Î¼,Î½)- pseudo almost periodic (respectively, (Î¼,Î½)-pseudo almost automorphic) solutions to some nonautonomous partial evolution equations in Banach spaces. A few illustrative examples will be discussed at the end of the paper.